Standardization Study of Antifertility Drug - Pippalyadiyoga - D. Shaila; M. K. Santosh; Biswajit Chowdhury; I. Rajyalakshmi; I. Sanjeevarao (E-Journal of Chemistry, 2005)
The present paper deals with the standardization study of pippalyadiyoga powder. It is used as a long acting contraceptive. The standardization of compound drug has been achieved by physico-chemical analysis and high performance liquid chromatography (HPLC) fingerprint studies. Quantitative evaluation of borax in pippalyadiyoga showed 19.08% as sodium borate. RP-HPLC was performed using methanol and water as mobile phase. The detection and quantification was performed at a wavelength of 345 nm. Linearity of detector response for piperine was between the concentrations 0.005% to 0.1%. The correlation coefficient obtained for the linearity was 0.998. The recovery value of standard piperine was 99.4%. Low value of standard deviation and coefficient of variation are indicative of high precision of the method. Quantitative evaluation of piperine in pippalyadiyoga was found to be 0.339%.